Pilot study of a novel multi‐functional noninvasive prenatal test on fetus aneuploidy, copy number variation, and single‐gene disorder screening. Issue 4 (14th February 2019) - Luo, Yuqin; Jia, Bei; Yan, Kai; Liu, Siping; Song, Xiaojie; Chen, Mingfa; Jin, Fan; Du, Yang; Wang, Juan; Hong, Yan; Cao, Sha; Li, Dawei; et al.
Abstract: Background: The noninvasive prenatal testing (NIPT) has been successfully used in the clinical screening of fetal trisomy 13, 18, and 21 in the last few years and researches on detecting sub‐chromosomal copy number variations (CNVs) and monogenic diseases are also in progress. To date, multiple tests are needed in order to complete a full set of fetus disorder screening, which is costly and time consuming. Therefore, an integrated 3‐in‐1 NIPT approach will be in great demand by routine clinical practice in the near future. Methods: We designed a target capture sequencing panel with an associate bioinformatics pipeline to create a novel multi‐functional NIPT method and we evaluated its performance by testing 22 clinical samples containing aneuploidy, CNV, and single‐gene disorder. Chromosomal aneuploidy and CNV were detected based on the Z‐value approach, whereas single‐gene disorder was identified by using the "pseudo‐tetraploid" model to estimate the best‐suited genotype for each locus. Results: The performance of this newly constructed 3‐in‐1 system was promising. We achieved a 100% detection rate for chromosomal aneuploidies (7/7), a 100% diagnosis rate for fetus CNVs larger than 20 Mb (3/3), and an 86.4% accuracy for single‐gene disorder screening (19/22). Conclusion: For the first time, we showed that it is possible to use just a single NIPT test to detect three distinct types of fetus disorder and laid a foundation for developing a cheaper, faster, and multi‐functional NIPT method in the future. Abstract : We developed a novel multi‐functional NIPT method to screen fetus aneuploidy, copy number variation and single‐gene disorder within one single test. The detections rates for fetus aneuploidies, CNVs larger than 20Mb, and single‐gene disorders were 100% (7/7), 100% (3/3), and 86.4% (19/22), respectively. For the first time, we showed that it is possible to use a single NIPT test to detect three distinct types of fetus gene disorder and laid a foundation for developing a cheaper, faster, and multi‐functional non‐invasive prenatal test in the future.